To compare creatinine estimation by jaffe and enzymatic method - Sahaya Merina Augustin; Ravi Prakash Deshpande; Girish Konasagara Shanthaveeranna (Wolters Kluwer Medknow Publications, 2022)
Introduction: Creatinine in urine and serum are used in the assessment of renal function. It is commonly estimated by Jaffe's and enzymatic method. In many institutions, serum creatinine is estimated by (POCT) Point of care testing device (Enzymatic method) and follow-up of the patients with creatinine results by other methods, analyzed in the Biochemistry laboratory. If the results of POCT do not correlate with the Jaffe method, it leads to differences in serum creatinine values and wrong treatment decisions during the follow-up of the patients. Hence, this study was done to know the difference between the two methods in a tertiary care hospital. Aim and Objective: To estimate creatinine by Jaffe's and enzymatic method and to compare the serum creatinine values between the two methods. Materials and Methods: It is an observational cross-sectional study, for a period of 17 months from November 2018 to March 2020. Seventy-five samples were analyzed for serum creatinine by Jaffe's method in the Biochemistry laboratory and by enzymatic method in the emergency department in POCT device. Results: Mean differences between Jaffe's and enzymatic method were −0.063 mg/dL, 0.070 mg/dL, 0.198 mg/dL, and 0.0685 in Group I, II, III, and all the groups together. The overall intraclass correlation coefficient including all the three groups (0.995) indicates a very good correlation between the two methods. Conclusion: Our study showed a good agreement and good correlation between the two methods, which is similar to other studies analyzed on same instrument.